Synthesis and characterisation of metallosurfactants as Carbon Dioxide viscosity modifier - R Abdosalam Khadega, Mohamed Azmi, (Universiti Pendidikan Sultan Idris, 2017)
Synthesis and characterisation of metallosurfactants as Carbon Dioxide viscosity modifier by R Abdosalam Khadega, Mohamed Azmi,